PERAN PERPUSTAKAAN ISLAM DALAM PERADABAN ISLAM - Adiningsih, Sekar Ayu (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Islamic libraries play an important role in Islamic development and civilization. The Islamic library also a center for intellectualism and maintenance of Islamic cultural heritage. Through collections of classical books, ancient manuscripts and works of leading scholars, Islamic libraries play a vital role in preserving and disseminating knowledge of Islamic religion, history, science and literature. This research method uses descriptive and qualitative methods, and is based on a literature review. Researching literature involves searching for theoretical references related to the topic being discussed, looking for references from books, academic papers, research reports, magazines, research results, etc. The results of this research show that Islamic libraries are important institutions in Islamic civilization, which contribute significantly to the development of science, the spread of education, and the preservation of intellectual heritage. Their extensive collections, their role as centers of learning and research, and their commitment to the preservation of knowledge make them vital centers of knowledge and culture. Understanding the history and heritage of these libraries is essential to appreciate their invaluable contribution to Islamic civilization & the world as a whole.